2017
DOI: 10.1063/1.4989476
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of star polymer solutions: A coarse-grained study

Abstract: We consider a coarse-grained (CG) model with pairwise interactions, suitable to describe lowdensity solutions of star-branched polymers of functionality f . Each macromolecule is represented by a CG molecule with (f + 1) interaction sites, which captures the star topology. Potentials are obtained by requiring the CG model to reproduce a set of distribution functions computed in the microscopic model in the zero-density limit. Explicit results are given for f = 6, 12 and 40. We use the CG model to compute the o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…Yet, its reliability depends on the adequate choice of essential degrees of freedom (i.e., electronic, nuclear, atomic, and molecular) and of interaction potentials (i.e., quantum or classical mechanics) governing the motion along these degrees of freedom . Different levels of coarse-grained representations have been successfully combined with MD simulations to investigate the structural and thermodynamic properties of conventional polymer brushes. However, fewer systematic studies have reported on atomistic MD simulations of polymer brushes. These reports have demonstrated the requirement of an atomic description to properly account for the role of a solvent on polymer chain dynamics and interactions, and ion-specific effects on the structure, mechanics, and interfacial softness of polymer brushes. Moreover, reliable coarse-grained models are expected to reproduce molecular properties of the underlying atomistic system so that accurate atomistic models are also necessary for the development of robust coarse-grained (CG) models . Furthermore, the properties of strong and weak polyelectrolyte brushes have been extensively investigated via continuum models based on the scaling , and self-consistent field theories.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, its reliability depends on the adequate choice of essential degrees of freedom (i.e., electronic, nuclear, atomic, and molecular) and of interaction potentials (i.e., quantum or classical mechanics) governing the motion along these degrees of freedom . Different levels of coarse-grained representations have been successfully combined with MD simulations to investigate the structural and thermodynamic properties of conventional polymer brushes. However, fewer systematic studies have reported on atomistic MD simulations of polymer brushes. These reports have demonstrated the requirement of an atomic description to properly account for the role of a solvent on polymer chain dynamics and interactions, and ion-specific effects on the structure, mechanics, and interfacial softness of polymer brushes. Moreover, reliable coarse-grained models are expected to reproduce molecular properties of the underlying atomistic system so that accurate atomistic models are also necessary for the development of robust coarse-grained (CG) models . Furthermore, the properties of strong and weak polyelectrolyte brushes have been extensively investigated via continuum models based on the scaling , and self-consistent field theories.…”
Section: Introductionmentioning
confidence: 99%
“…The price one pays for the simplification is that the PMF is intrinsically many-body in nature: even if the energetic landscape of the original microscopic system comprises only pair potentials among its constituent atoms, once the resolution reduction is performed a whole hierarchy of interactions appears that involve, in addition to pairwise terms, triplets of CG sites, quadruplets, and so on ( Dijkstra et al, 1999 ). These many-body components can play a key role in generating, and comprehend the origin of, the correct large-scale behavior of a system ( D’Adamo et al, 2015 ; Menichetti et al, 2017 ), such as, in the case of proteins, secondary structure motifs ( Kolinski et al, 1993 ; Derreumaux, 1999 ; Bereau and Deserno, 2009 ; Liwo, 2013 ; Sieradzan et al, 2017 ); at the same time, however, their presence makes the exact determination of a PMF largely unfeasible in practice, except for very simple microscopic models ( Diggins et al, 2018 ).…”
Section: Coarse-grained Modeling: General Frameworkmentioning
confidence: 99%
“…Pioneer experimental works studied rheological properties of star polymers in melts , and concentrated solution , and pioneer theoretical studies derived the main features of the structure and relaxation dynamics of star molecules in solution. The dual character of star molecules (from polymeric chains to soft colloids) has also motivated more recent studies of the thermodynamics of star polymer solutions and their phase diagrams of packing . Moreover, the spherical shape and internal complexity of star polymers make them an excellent choice to test coarse-graining theories. , …”
Section: Introductionmentioning
confidence: 99%
“…The dual character of star molecules (from polymeric chains to soft colloids) has also motivated more recent studies of the thermodynamics of star polymer solutions and their phase diagrams of packing . Moreover, the spherical shape and internal complexity of star polymers make them an excellent choice to test coarse-graining theories. , …”
Section: Introductionmentioning
confidence: 99%